Beyond protein binding: recent advances in screening DNA-encoded libraries. Issue 89 (21st October 2019) - Kodadek, Thomas; Paciaroni, Nicholas G.; Balzarini, Madeline; Dickson, Paige
Abstract : DNA-encoded libraries are usually screened against tagged proteins to identify ligands, but many other screening modalities either have been, or likely will be, developed that expand the utility of these libraries as a source of bioactive molecules. Abstract : DNA-encoded library (DEL) screening has emerged as an important method for early stage drug and probe molecule discovery. The vast majority of screens using DELs have been relatively simple binding assays. The library is incubated with a target molecule, which is almost always a protein, and the DNAs that remain associated with the target after thorough washing are amplified and deep sequenced to reveal the chemical structures of the ligands they encode. Recently however, a number of different screening formats have been introduced that demand more than simple binding. These include a format that demands hits exhibit high selectivity for target vs. off-targets, a protocol to screen for enzyme inhibitors and another to identify organocatalysts in a DEL. These and other novel assay formats are reviewed in this article. We also consider some of the most significant remaining challenges in DEL assay development.